CURRENT STATE OF INVESTMENT ENVIRONMENT OF UKRAINE THROUGH THE PRISM OF INTERNATIONAL RATING - Halaziuk , N.M. (The actual problems of regional economy development, 2023)
Modern business conditions are characterized by rapid technological development, so investments are an extremely important means of stimulating progressive structural changes in the economy of each country. Ukraine is on the path of economic transformation, under such conditions, improving the investment environment is one of the main directions of state policy at the current stage. The Ukrainian investment environment attracts and repels at the same time. Ukraine occupies a strategic geographical position, has rich natural resources and a highly educated workforce, which makes it attractive for investment, however, it has not yet reached its expected potential, since today there is a full-scale war on the territory of the country, and the state's intervention in the functioning of markets, administrative obstacles that hinder the conduct of business have not been eliminated. The study of positive and negative aspects of investment activity in the territory of our country is becoming more and more relevant. The study of issues related to the assessment and analysis of the Ukrainian investment environment is the object of research by many scientists. The value of scientific works with their theoretical and practical studies is quite high, but many aspects require further research. Thus, in order to form an effective strategy and determine the tools for attracting foreign investment, it is necessary to monitor the current state of the Ukrainian investment environment and evaluate the value of indicators of its investment attractiveness. The object of the study is the modern Ukrainian investment environment. The subject of the study is the practice of using international rating data to monitor the investment environment of Ukraine in today's conditions. The purpose of the article is to determine the main factors that ensure the country's investment image in the international arena, taking into account the realities of the modern world. The main research methods used in the research were general economic and special scientific methods, including the abstract method, analysis and synthesis, as well as the statistical method. An analytical study of the investment environment in Ukraine was conducted, international investment indices were considered, and Ukraine's position in international investment ratings was determined. The results of the study were the conclusions made on the basis of the study of investment attractiveness indices, the state of the investment environment of Ukraine through the prism of international rating. The practical significance of the scientific research and its results is the study of the determining factors of improving the investment environment, investment attractiveness and international image of Ukraine.